2007
DOI: 10.1177/089875640702400402
|View full text |Cite
|
Sign up to set email alerts
|

Histological Evaluation of the Pulp in Teeth from Dogs with Naturally Occurring Periodontal Disease

Abstract: The purpose of this investigation was to evaluate the pulp of dog teeth affected by advanced periodontal disease. Histological examination was done on demineralized teeth extracted during clinical treatment of mature, client owned small and medium-size breed dogs with either good periodontal health or with advanced naturally occurring periodontal disease. Routinely stained sections from 5 clinically normal teeth and 22 teeth with advanced periodontitis from dogs between 5 and 12-years of age were examined usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 45 publications
2
14
0
Order By: Relevance
“…Teeth affected with advanced periodontitis and results specific to periodontally affected teeth have revealed acute and chronic pulpitis, vascular congestion, and pulp necrosis. 12 Various studies have confirmed the observations of the study, however many other studies have reported differing results. In an extensive study conducted by Mazur and Massler, it was observed that severity or presence of periodontal disease had no effect on the pulp, with similar mild to severe pulp histologic changes being observed in both healthy control and periodontally affected teeth.…”
Section: Johsrsupporting
confidence: 68%
“…Teeth affected with advanced periodontitis and results specific to periodontally affected teeth have revealed acute and chronic pulpitis, vascular congestion, and pulp necrosis. 12 Various studies have confirmed the observations of the study, however many other studies have reported differing results. In an extensive study conducted by Mazur and Massler, it was observed that severity or presence of periodontal disease had no effect on the pulp, with similar mild to severe pulp histologic changes being observed in both healthy control and periodontally affected teeth.…”
Section: Johsrsupporting
confidence: 68%
“…[15] Nemec et al showed that findings related to periodontally affected teeth included acute and chronic pulpitis, vascular congestion and pulp necrosis. [16] In a contradictory to this study and several studies, many other studies have reported conflicting results. In a study by Mazur and Massler, they disagree that a periodontal disease has any effect on the pulp.…”
Section: Discussionmentioning
confidence: 86%
“…(2007) also showed the advanced periodontitis affecting teeth and findings specific to periodontally affected teeth included acute and chronic pulpitis, vascular congestion, and pulp necrosis. [19]…”
Section: Discussionmentioning
confidence: 99%